The Role of Anemia in Pregnancy in the Incidence of Post Partum Hemorrhage in Maternal Maternity at the Hospital in Sidoarjo, Indonesia - Mukarromatul Khoiroh; Nurul Azizah (Indonesian Journal of Cultural and Community Development, 2019)
Postpartum hemorrhage is bleeding that occurs after the birth of the baby, placenta, and 2 hours after the placenta is born. One of the causes is anemia. Research in 2015, 60% of 100 mothers giving birth at RSIA Kirana Taman Sidoarjo experienced postpartum hemorrhage. The aim of the study was to determine the relationship of anemia in pregnancy with the incidence of postpartum hemorrhage in labor mothers. The study design used an analytical survey with a retrospective method. The population of 206 maternity mothers was taken with simple random sampling technique as many as 136 samples in August 2017. Data were analyzed by Chi Square statistical test with 0.05. The results showed that postpartum hemorrhage was more experienced by mothers with anemia (66.7%) than those without anemia (26.2%). While those who did not experience postpartum hemorrhage were more experienced by mothers who were not anemic (73.8%) than those who were anemic (33.3%). Chi square test results (p=0.000 <0.05), which means there is a relationship of anemia in pregnancy with the incidence of postpartum hemorrhage in labor mothers. Conclusions of the study were the relationship of anemia in pregnancy with the incidence of postpartum hemorrhage in labor mothers. It is expected that midwives and doctors conduct early detection of anemia so that appropriate care can be carried out.